Los territorios de la arquitectura : el proyecto análogo : Opus5-2018_20 (2018)
"The work sector is inscribed between the avenues Ciudad de Quito and 68, Calle 80 and the Salitre park. The zone is composed of the neighborhoods Jorge Eliécer Gaitán, 12 de octubre, San Fernando, San Fernando Occidental, Simón Bolívar, Metropolis, José Joaquín Vargas, Popular Modelo and San Miguel; being mostly informal origin. The neighborhoods are composed of housing from one to three floors where sometimes the first floor is used for commercial industry. In most of the edges of the sector are located the residential complexes which were built in recent years and which end up consolidating the area. The chosen area is located in the San Fernando neighborhood, which has as its limits Avenida 30 until Carrera 68 and Calle 72 and 68. The place presents blocks of singular typologies since the path of the roads transform and change the predominant orthogonal urban frame of the sector. In the same way, these two great roads allow buildings facing these to be commercial and of constant flow. There are unique urban elements such as the Barrios Unidos Park together with the San Fernando Rey Church, The Chapinero Hospital, The Jorge Eliécer Gaitán School and the Police Station. The blocks between 60 and 58 avenue, calle 68 and 71 were chosen then. These blocks were developed between 1958 and 1970, at the time of their construction, the western side was destined for free area or public space, but in the following years disappeared to make way for the construction of blocks. Therefore the intentions of the project seek to liberate city land to generate public, collective and private space. The above is achieved through the recomposition and re-qualification of the city."--Tomado del Formato de Documento de Grado.